2013
DOI: 10.1007/s00264-013-1822-8
|View full text |Cite
|
Sign up to set email alerts
|

Plate fixation for proximal chevron osteotomy has greater risk for hallux valgus recurrence than Kirschner wire fixation

Abstract: Purpose The purpose of this study was to compare the results of hallux valgus surgery between feet fixed with Kirschner wires and those fixed with a plate and screws. Methods Between December 2008 and November 2009, 53 patients (62 feet) were treated with proximal chevron osteotomy and distal soft tissue procedure for symptomatic moderate to severe hallux valgus deformity. Thirty-four patients (41 feet) were stabilised with Kirschner wires (K-wire group) and 19 patients (21 feet) were stabilised with a locking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…We also Page 12 of 21 A c c e p t e d M a n u s c r i p t recognize a disadvantage of the technique performed with the use of K-wires that can potentially provide a conduit for the introduction of bacteria to the operative area, or can be associated with an unpleasant sense due to pain in the surrounding skin or undesirable skin traction [35]. However, in the present study there were no complications regarding K-wire placement, and, as also shown in the literature, the use of K-wires has demonstrated favored outcome with minimal complications [36]. In addition, with the removal of the wire six weeks postoperatively, patient was entirely free of any internal or external fixation`s implant.…”
Section: Page 11 Of 21supporting
confidence: 64%
“…We also Page 12 of 21 A c c e p t e d M a n u s c r i p t recognize a disadvantage of the technique performed with the use of K-wires that can potentially provide a conduit for the introduction of bacteria to the operative area, or can be associated with an unpleasant sense due to pain in the surrounding skin or undesirable skin traction [35]. However, in the present study there were no complications regarding K-wire placement, and, as also shown in the literature, the use of K-wires has demonstrated favored outcome with minimal complications [36]. In addition, with the removal of the wire six weeks postoperatively, patient was entirely free of any internal or external fixation`s implant.…”
Section: Page 11 Of 21supporting
confidence: 64%
“…Patients should be cautioned of this possibility and advised to return to normal walking activities gradually during the fourth postoperative month. We found the frequency of recurrence of metatarsus primus varus to be low, and the recurrences to be mild when compared with 10% to 33% reported after osteotomy [4,18]. This could be attributed to the first metatarsal stability issue by intermetatarsal fibrous bonding during the osteodesis.…”
Section: Discussionmentioning
confidence: 63%
“…This angle remained constant from the time of union to the last follow-up. The mean pre-operative HVA was 39 (range 21-52) degrees, and the mean postoperative HVA was 11.8 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) degrees. The mean HVA at the last followup was 12.7 (range 6-30) degrees.…”
Section: Resultsmentioning
confidence: 99%
“…Different types of proximal metatarsal osteotomies have been used over the last decades including proximal crescentic osteotomy [7], proximal chevron osteotomy [8,9], scarf osteotomy [10,11], Ludloff osteotomy [12], Mau osteotomy [13], modified Mau [14], lateral closing wedge basal osteotomy [15] and medial opening wedge basal osteotomy [16].…”
Section: Introductionmentioning
confidence: 99%